The New Soliton Configurations of the 3D Fractional Model in Arising Shallow Water Waves - Alam, Md. Nur; Talib, Imran; Tunç, Cemil (International journal of applied and computational mathematics, 2023)
This paper utilizes the analytical technique (AT) to investigate the new soliton configurations (NSCs) of the nonlinear 3D fractional model (NL3DFM) with its spatial and temporal variables (STVs) which is stretch for the KdV model. The procedure gives a diversity of NSCs to the scientific literature. A lot of new computing soliton configurations have been taken. Some soliton configurations are shaped in density plots (DPs), contour plots (CPs), 2D plots (2DPs) and 3D plots (3DPs) that represent the unidirectional generation of short amplitude deep waves on the surface of acoustic and hydro-magnetic fluctuations in a channel especially for shallow water (SW). Moreover, some effects are manifested via numerical simulations (NSs) that confirm the originality of our task. Besides, we note that totally the NSCs are novel and an outstanding influence to solitary wave theory's existing literature. The chief knowledge of this investigation understanding novel NSCs and hence NSCs of this novel perception through its STVs and NL3DFM. The created process can be implemented to numerous other NL3DFMs. Comparing our studied answers and that got in earlier written scientific papers offers the novelty of our examination. The AT could also be implemented to get NSCs for other 3D-fractional models.